Common predictors of cervical cancer related mortality in Ethiopia. A systematic review and meta-analysis - Hunduma Dina Hambisa; Berhane Teklay Asfaha; Biniam Ambisa; Abebech Gudeta Beyisho (BMC Public Health, 2024)
Abstract Background Cervical cancer accounts for 7.5% of all female cancer related deaths worldwide; peaking between the ages of 35 and 65, and not only kills young women but also destroys families with young children. Objective This review was intended to measure national level magnitude and the most common predictors of cervical cancer related mortality in Ethiopia. Methods Common Public databases like Science Direct, Embase, the Cochrane Library, and PubMed were thoroughly searched. The STATA 14 and Rev-Manager 5.3 statistical software packages were used for analysis, as well as a standardized data abstraction tool created in Microsoft Excel. The Cochrane Q-test statistics and the I2 test were used to assess non-uniformity. The pooled magnitude and predictors of cervical cancer related mortality were estimated using fixed-effect and random-effect models, respectively. Result The pooled mortality among cervical cancer patients was estimated that 16.39% at 95% confidence level fall in 13.89–18.88% in Ethiopia. The most common predictors of cervical cancer related mortality were late diagnosed, radiation therapy alone, and Being anemic were identified by this review. Among cervical cancer treatment modalities effectiveness of surgery with adjuvant therapy was also approved in this meta-analysis. Conclusion and recommendation In this study high cervical cancer-related mortality was reported as compared to national strategies to alleviate cervical cancer related mortality. Advanced implementation of cervical cancer screening at the national level for early diagnosis, anaemia detection, and combination anticancer therapy during initiation, as well as combination therapy, is critical to improve cervical cancer patient survival and decreasing mortality rates.